2021
DOI: 10.1186/s12917-021-02843-8
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive squamous cell carcinoma of the cranium of a dog

Abstract: Background The authors report a case of keratinized squamous cell carcinoma (SCC) in a 14-year-old dog with extensive cranial bone invasion. To our knowledge, this is the first description of such a case of cranial keratinized SCC with aggressive generalized osteolysis described in a dog. Case presentation The 14-year-old dog was referred for radiological examination with suspicion of head trauma with clinical signs of head deformation, exophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…The same year saw reports on cutaneous cases in mixed-breed dogs, American pit bulls, boxers, and English pointers (Dos Anjos et al, 2019). From 2020 to 2021, there were reports of SCC in the cranium and oral cavity (Simčič et al, 2020;Łojszczyk et al, 2021). In the current case study, SCC was near the left submandibular region of a dog, which is rarely found.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…The same year saw reports on cutaneous cases in mixed-breed dogs, American pit bulls, boxers, and English pointers (Dos Anjos et al, 2019). From 2020 to 2021, there were reports of SCC in the cranium and oral cavity (Simčič et al, 2020;Łojszczyk et al, 2021). In the current case study, SCC was near the left submandibular region of a dog, which is rarely found.…”
Section: Discussionmentioning
confidence: 47%
“…As previously reported, SCC is commonly found in dogs with an average age of 8.8 years (Willcox et al, 2019). In addition, some previous reports found an average age of 10 years (Lascelles et al, 2000), but the condition can be found from 4 months to 14 years of age (Łojszczyk et al, 2021;Sharma et al, 2021). The effect of gender on cases of SCC is unclear.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the meningioma most likely induced the skull osteolysis reported here, it is important to mention the presence of the presumed adenocarcinomatous metastasis in this case, which might also have played a role in the lytic process. Indeed, other tumour types or pathological conditions inducing skull osteolysis have been reported in dogs and cats, such as squamous cell carcinoma, 14 choroid plexus carcinoma, 15 glioma, 16 pulmonary adenosquamous carcinoma metastases, 17 skull osteomyelitis 18 and intra cranial epidural tuberculoma. 19 In human medicine, osteolysis associated with intracranial meningiomas is a very rare finding and might be related to type 2 matrix metalloproteinase (MMP) expression.…”
Section: Discussionmentioning
confidence: 99%